The Implementation Analysis Of Lamport Scheme With Sha-256 On Mobile E-Office - Hendra Widodo; Mardiana Mardiana; Melvi Melvi; Ardian Ulvan; Pattarakorn Sajjaporn Nuttachot (International Journal of Artificial Intelligence Research, 2021)
Electronic administration system is one of the best solutions in the current digital era, electronic-based systems are considered to make it easier for an organization to process data and can reduce the possibility of data loss due to human error or natural disasters. The current administrative data management application is called the Electronic Office (E-Office). The E-Office handles data for  incoming mail, outgoing mail and mail disposition. There are frequent delays in receiving information and validating letter files that are still carried out using physical files, so the mobile e-office is a solution that can be used by an agency to make it easier  for workers to access information more quickly and can be done anywhere. Data security is an important thing that needs to be considered in an electronic transaction, so this research will add data security to the mobile e-office using sha-256 and lamport schemes. We present data on the results of this mobile e-office test on mobile devices and virtual private servers (vps), the data is in the form of functional application performance testing results and records of processing time performed by mobile and vps devices. From this  data an analysis will be carried out to determine the appropriateness of the devices that can be used in running a mobile e-office.